Pengaruh Pengalaman Kerja dan Pelatihan Terhadap Kinerja Pegawai dan Kompetensi Kerja sebagai Variabel Intervening pada Pegawai Puskesmas Kambang Kabupaten Pesisir Selatan - Riska Afrianti Eka Putri; Marta Widian Sari; Mutia Seplinda (Journal of Management and Creative Business, 2024)
This research aims to examine the influence of work experience and training on employee performance with work competency as an intervening variable using primary data obtained by distributing questionnaires to 55 employees as respondents, namely employees of the Kambang Health Center, Pesisir Selatan Regency. In this research, Structrual Equation Modeling (SEM) analysis tools were used using Partial Least Square (PLS). The research results show that (1) There is a positive and significant influence of Work Experience on Job Competency (2) There is a positive and insignificant influence of Training on Job Competency (3) There is a positive and insignificant influence of Work Experience on Employee Performance (4) There is a positive influence Training has a positive and significant effect on Employee Performance (5) There is a positive and significant influence of Career Competency on Employee Performance (6) There is a positive and significant influence of Work Experience on Employee Performance through Work Competency (7) There is a positive and insignificant influence of Training on Employee Performance through Competency Work (8) The contribution of the Work Experience and Training variables to Work Competence is 0.627 or 62.7%, while the remaining 37.3% is influenced by other variables not determined in this research. (9) The contribution of work experience and training variables to employee performance is 0.902 or 90.2%, while the remaining 0.98% is influenced by other variables not determined in this research.